PENGGUNAAN ALAT PELINDUNG DIRI (APD) DAN KADAR HEMOGLOBIN PADA PETANI PENGGUNA PESTISIDA DI DESA RIANG GEDE, KECAMATAN PENEBEL, TABANAN - Suryadhi, Made Ayu Hitapretiwi; Suryadhi, Putu Ayu Rhamani; Purnama, I Gede Herry (ARCHIVE OF COMMUNITY HEALTH, 2013)
Pesticide use amongst farmers remains high in Bali. Pesticide use causes acute- to chronic- health effects. This study focusses on assessing the use of protective gear amongst farmers using pesticides and measuring their hemoglobin level.This was a cross-sectional study in 71 male farmers in the village of Riang Gede, Penebel, Tabanan, Bali. Data was collected by interview and blood test. Analysis was performed using SPSS 18.0.Mean age of farmers was 51,2 years and mean body mass index (BMI) was 21,5 kg/m2. Most of the farmershad an education level of primary school. Use of full protective gear was low for mask, boot, eye-protection, and gloves. Hemoglobin level was abnormal in 49,3% of farmers with a mean hemoglobin level of 12,2 g/dl which was lower than that of the normal population.This study showedthat the use of appropriate protective gear is low and that pesticide use might contribute to the lowering of hemoglobin level.
Keywords: Pesticide, Hemoglobin, Protectie gear